The Development of 21st Century Skills through PSL Practicum and HOT Lab in Science Education - Zulfa; Adam Malik (Department of Physics Education, Universitas Mataram, 2025)
Laboratory work has traditionally served as an essential component of science education, offering students the opportunity to experience science directly through observation and experimentation. However, in the context of 21st-century learning, traditional laboratory approaches are no longer sufficient. The current educational landscape demands learning environments that not only facilitate conceptual understanding but also cultivate essential competencies such as critical thinking, problem-solving, creativity, communication, and collaboration. In response to these challenges, two innovative laboratory models have emerged, namely the Problem-Solving Laboratory (PSL) and the Higher Order Thinking Laboratory (HOT Lab). This study aims to explore how these laboratory designs contribute to the development of 21st-century skills among high school students. Using a descriptive quantitative approach, the research involved 120 students from schools that have implemented PSL and HOT Lab activities. Data were gathered through a 25-item Likert-scale questionnaire and observation of laboratory sessions. The results indicated a positive shift in student skills, with 82 percent showing improvement in problem-solving, 78 percent in critical thinking, 75 percent in creativity, 68 percent in communication, and 63 percent in collaboration. Students also expressed higher levels of engagement, motivation, and enthusiasm during their participation in the laboratory sessions. These findings suggest that when laboratory learning is designed to promote inquiry, reflection, and contextual problem-solving, it can meaningfully enhance both cognitive and interpersonal skills. Furthermore, the study highlights the importance of active learning in fostering a dynamic and student-centered classroom atmosphere. Although the results are promising, the research also points to several practical challenges, such as the need for teacher training, sufficient resources, and adequate time allocation. Overall, PSL and HOT Lab represent effective strategies to support the holistic development of learners and provide a valuable framework for science educators seeking to align classroom practices with the demands of the 21st century.